3D seismic investigation of the structural and stratigraphic characteristics of the Pagasa Wedge, Southwest Palawan Basin, Philippines, and their tectonic implications. (1st April 2018) - Ilao, Kimberly A.; Morley, Christopher K.; Aurelio, Mario A.
Highlights: Pagasa wedge is predominantly composed of mass transport complexes. The wedge is probably dominated by gravity driven structures. The wedge is a late-stage feature following emplacement of the Palawan ophiolite. Nido Limestone shows thrusting both to the North and the Northwest. Abstract: The Pagasa Wedge is a poorly imaged deepwater orogenic wedge that has been variously interpreted as representing an accretionary prism, a former accretionary prism modified by thrusting onto a thinned continental margin, and a gravity-driven fold-thrust belt. This study, using 2D and 3D seismic data, together with well information indicates that at least the external part of the wedge is dominantly composed of mass transport complexes, capped by syn-kinematic sediments that have thrusts and normal faults superimposed upon them. Drilling shows that despite stratigraphic repetition of Eocene Middle Miocene units, there is stratigraphic omission of Oligocene and Early Miocene units. This absence suggests that mass transport processes have introduced the Eocene section into the wedge rather than tectonic thrusting. The accretionary prism stage (Oligocene) of the Central Palawan Ophiolite history appears to be marked by predominantly north-vergent deformation. The Deep Regional Unconformity (∼17 Ma) likely indicates the approximate time when obduction ceased in Palawan. The Pagasa Wedge is a late-stage product of the convergence history that was active in its final phase sometime above the top of the Nido Limestone (∼16 Ma) and the base of the Tabon Limestone in the Aboabo-A1X well (∼9 Ma). The top of the wedge is traditionally associated with the Middle Miocene Unconformity (MMU), However the presence of multiple unconformities, diachronous formation tops, local tectonic unconformities and regional diachronous events (e.g. migrating forebulges) all suggest simply giving a single age (or assigning a single unconformity, such as the MMU as defining the top of the Pagasa Wedge is inappropriate. The overall NE-SW trend of the wedge, and the dominant NW transport of structures within the wedge diverge from the more northerly transport direction determined from outcrops in Palawan, and also from the Nido Limestone in the SW part of the Pagasa Wedge. Possibly this NW transport direction is more related to gravity-driven structures responding to uplift of NE-SW Dangerous Grounds margin during the Middle Miocene (related to slab breakoff?) than it is to thrusting rooted in a plate boundary. The final modification of the wedge occurred when the effects of compression deformation on the wedge had largely ended, but gravity processes (in particular mass transport and normal faulting) still operated.